THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE FREIGHT INDUSTRY: A COMPREHENSIVE ANALYSIS - Mohini Thakkar (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
This comprehensive article explores the transformative impact of Artificial Intelligence (AI) on the freight industry, examining its applications, benefits, challenges, and prospects. It delves into how AI is revolutionizing key areas such as logistics optimization, predictive maintenance, demand forecasting, and inventory management. The article discusses the emergence of autonomous vehicles and drones in freight transport, highlighting their potential to reshape last-mile delivery and long-haul operations. Additionally, it analyzes the role of AI in enhancing customer service and communication through chatbots, virtual assistants, and advanced analytics. The article also addresses the significant challenges in AI integration, including data privacy concerns, cybersecurity risks, and the need for workforce adaptation. Looking towards the future, the article explores emerging technologies like blockchain-enabled smart contracts and AI-optimized warehousing, offering insights into how these innovations may further transform the industry. Through a critical examination of current implementations and future possibilities, this article provides a comprehensive overview of AI's role in shaping the future of global freight operations, emphasizing its potential to drive efficiency, sustainability, and innovation in the sector.